Collaboration Between the Indonesian National Police and the Community in Preventing Illegal Mining in the Tembelok Sea Area - Arlianto, Muhammad Harits; Basir, Basir; Dwilaksana, Chrysnanda (CV. Proaksara Global Transeduka, 2026)
Illegal tin mining in Tembelok Sea, West Bangka, has caused massive environmental impacts, such as coral reef damage, a 30% decrease in fish catches, and triggered unrest and social conflicts in coastal communities. This exploratory qualitative research aims to analyze collaboration strategies between the Indonesian National Police (Polri) and the community in preventing such illegal activities. Data were collected through interviews, observations, and document studies, then analyzed using the Law Enforcement Theory, Collaborative Policing, and Crime Prevention approaches. The research results show that joint patrols are an effective integrated strategy, integrating primary prevention approaches (socialization, “Alert Fishermen” training, drone/GIS technology), secondary (focused patrols, community reports), and tertiary (firm law enforcement, environmental rehabilitation). This collaboration is driven by inter-agency synergy (Polri, Indonesian Navy, Bakamla), active community participation, and open communication. However, challenges such as overlapping authorities, limited resources, intimidation of reporters, and lack of integrated data platforms still hinder its effectiveness. To ensure sustainability, it is recommended to establish a permanent task force, develop anonymous digital reporting applications, and launch alternative economic empowerment programs, such as seaweed cultivation. In conclusion, the Polri-community collaboration has the potential to create an inclusive and sustainable monitoring system to maintain the preservation of marine ecosystems and the socio-economic stability of the Tembelok coastal community.